EXPERIENCE OF TREATMENT OF JUVENILE POLYARTHRITIS WITH EYES LESION WITH ADALIMUMAB - A.O. Lisitsin; E.I. Alexeeva; T.M. Bzarova; S.I. Valieva; A.M. Chomakhidze; K.B. Isaeva; E.G. Chistyakova; R.V. Denisova; E.Yu. Gudkova; N.A. Karagulyan (Вопросы современной педиатрии, 2008)
A case report of early debut and severe course of juvenile poly arthritis with eyes lesion refractory to classic immuno suppressive agents is presented in this article. Successful application of biological agent adalimumab is described: acute inflammatory alterations in affected joints were stopped by 49 the week. Range of motions in affected joints was recovered. The remission of veitis, normalization of indicators of disease activity (ESR, concentration of creactive protein in blood plasma) was registered by 89 th week. Key words: children, juvenile rheumatoid arthritis, rheumatoid uveitis, adalimumab.